2001
DOI: 10.1161/01.cir.103.18.2254
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Trial of Intravenous Immune Globulin in Recent-Onset Dilated Cardiomyopathy

Abstract: These results suggest that for patients with recent-onset dilated cardiomyopathy, IVIG does not augment the improvement in LVEF. However, in this overall cohort, LVEF improved significantly during follow-up, and the short-term prognosis remains favorable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
271
2
14

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 519 publications
(291 citation statements)
references
References 19 publications
4
271
2
14
Order By: Relevance
“…The longterm sequelae of viral myocarditis appear to be related to abnormal cellular and humoral immunity, many clinicians believe that immunosuppression should be beneWcial for myocarditis treatment, but has not shown to be eVective as conventional treatment for acute myocarditis [16,17]. Early trials of antiviral therapies, such as interferon, suggest a potential therapeutic role but require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The longterm sequelae of viral myocarditis appear to be related to abnormal cellular and humoral immunity, many clinicians believe that immunosuppression should be beneWcial for myocarditis treatment, but has not shown to be eVective as conventional treatment for acute myocarditis [16,17]. Early trials of antiviral therapies, such as interferon, suggest a potential therapeutic role but require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It can therefore be assumed that the optimal pharmacological treatment of heart failure according to guidelines can cause a positive effect in patients with ICM although this has not been convincingly demonstrated in a placebo-controlled study yet. In agreement with this, it was suggested that the increasing chance for LV function improvement in recent studies compared with older data was associated with advances in pharmacological therapy 42 . Also some experimental data as well as clinical studies confirm this.…”
Section: Discussionmentioning
confidence: 66%
“…39 In our previous study, exogenously administered IL-10, 15 or the gene transfer therapy of IL-10, 16 improved myocardial lesion in our model of viral myocarditis. In this study, gene expression of IL-10 in the heart was increased in mice treated with FLC, suggesting that a part of the effect of FLC might be attributable to this effect.…”
Section: Discussionmentioning
confidence: 68%